Narrazione eccentrica e testimonianza in Gomorra di Roberto Saviano - Bozzi, Francesco (Incontri. Rivista europea di studi italiani, 2015)
Eccentric Narration and Testimony in Roberto Saviano’s Gomorra If post-modern literature is often assumed to be characterized by the aporetic fusion of fictional and non-fictional contents, forms and structures, post-modern literary criticism seems to still struggle to avoid analyzing contemporary literature without leading itself back to the two static, dichotomous categories of fiction and non-fiction. This article attempts to penetrate the narrative structure of one of the most controversial Italian contemporary novels, Gomorra. It interprets this structure with the help of these two categories which are not considered stable and generative with respect to the narration itself, but are rather seen as derivative refractions of the hybridity of Saviano’s novel. In order to achieve this goal a comparison is made between three different, yet complementary texts. Firstly, it analyzes the continuity in narrative structure between Truman Capote’s non-fiction novel In Cold Blood and Gomorra. Moreover, it identifies the points of divergence that turn Saviano’s novel into an independent phenomenon of post-modern Italian literature. This divergence will be compared to the definition of Unidentified Narrative Objects (U.N.O.) proposed by Wu Ming in their programmatic essay New Italian Epic. Finally, it examines the connection between narration and testimony in Saviano’s Gomorra through Jacques Derrida’s theoretical conception in Demeure: Fiction and Testimony.